Distance and Similarity Measures for Octahedron Sets and Their Application to MCGDM Problems - Güzide Şenel; Jeong-Gon Lee; Kul Hur (Mathematics, 2020)
In this paper, in order to apply the concept of octahedron sets to multi-criteria group decision-making problems, we define several similarity and distance measures for octahedron sets. We present a multi-criteria group decision-making method with linguistic variables in octahedron set environment. We give a numerical example for multi-criteria group decision-making problems.